The most 5' truncating homozygous mutation of WNT1 in siblings with osteogenesis imperfecta with a variable degree of brain anomalies: a case report - Chulaluck Kuptanon; Chalurmpon Srichomthong; Apiruk Sangsin; Dool Kovitvanitcha; Kanya Suphapeetiporn; Vorasuk Shotelersuk (BMC, 2018)
Abstract Background WNT1 mutations cause bone fragility as well as brain anomalies. There are some reported cases of WNT1 mutations with normal cognition. Genotype and phenotype correlation of WNT1 mutations has not been established. Case presentation Here we present two female siblings with osteogenesis imperfecta (OI) born to a consanguineous couple. Both sustained severe bone deformities. However, only the younger had severe brain anomalies resulting in an early death from pneumonia, while the older had normal intellectual development. Next generation sequencing showed a homozygous mutation, c.6delG, p.Leu3Serfs*36 in WNT1. To our knowledge, it is the most 5' truncating mutation to date. Conclusion This report emphasizes the intrafamilial variability of brain anomalies found in this OI type and suggests that WNT1 may not be necessary for normal human cognitive development.